Novel Cell Wall Antifungals Reveal a Special Synergistic Activity in pbr1 Mutants Resistant to the Glucan Synthesis Antifungals Papulacandins and Echinocandins - Berzaghi, Rodrigo; Agócs, Attila; Curto, María A.; Gulyás-Fekete, Gergely; Kocsis, Béla; Ribas, Juan C.; Lóránd, Tamás (Frontiers in Microbiology, 2019)
A series of 4-(arylmethylene)-3-isochromanones have been prepared with base catalyzed Knoevenagel condensation starting from 3-isochromanone and aromatic aldehydes. The outcome of the reaction- the isomeric composition of the products depends on the aromatic aldehyde applied. These reactions afforded mostly the more stable E-diastereoismer, but some condensations resulted in the Z-diastereoisomer or mixture of the stereoisomers (1-16). The products showed antifungal effect against some pathogenic fungi - clinical isolates of Candida albicans, Criptococcus neoformans, etc. We wanted to extend this study and to synthesize a new generation of 4-(arylmethylene)-3-isochromanones. These condensations led mostly to E-diasteroisomers (17-30). The structure verifications were performed by FT IR, 1H and13C NMR methods. Both the 1-16 and the novel 17-30 compounds have been screened against the three yeast models, fission yeast Schizosaccharomyces pombe (wild type, and pbr1-6 and pbr1-8 mutants resistant to specific cell wall synthesis inhibitors), budding yeast Saccharomyces cerevisiae (wild type and pbr1-1) and pathogenic yeast C. albicans (wild type, ATCC 26555, 90028 and SC5314). Osmotic protection with sorbitol attenuated the inhibition suggesting a cell wall-specific antifungal effect. Moreover, the S. pombe wild type and mutant strains were tested for their resistant or sensitive in vitro β(1,3)-glucan synthase (GS) activity, finding both in vivo and in vitro a synergistic effect of higher sensitivity of the pbr1 mutants resistant to the specific GS inhibitors echinocandins. These results provide new insights into new strategies of combined antifungal therapy of GS inhibitors directed against spontaneous mutants resistant to echinocandins.